A critical analysis of the non-derogable rights in a state of emergency under the African system : the case of Ethiopia and Mozambique - Amaral, Leopoldo (University of Pretoria, 2006)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2005.